Cyclability in Lahore, Pakistan: Looking into Potential for Greener Urban Traveling - Aslam, S. Atif Bilal; E. Masoumi, Houshmand; Asim, Muhammad; Anwer, Izza (TeMA - Journal of Land Use, Mobility and Environment, 2018)
Measuring perceived or objective cyclability or bikeability has drawn less attention compared to walkability, particularly in developing countries like those in South Asia and the Middle East. This paper presents the results of a survey about cyclability in Lahore, Pakistan, focusing on human perceptions rather than the built environment. The overall sample included a total of 379 respondents from three socio-economic classes: those from lower socio-economic backgrounds accessing traditional/older bazaars, respondents from the middle socio-economic class accessing uptown bazaars, and respondents of higher socio-economic status accessing pedestrian shopping malls. The exploratory data collection was conducted in spring 2018 in Lahore by means of a short standard questionnaire with 19 questions, resulting in 17 categorical/dummy variables, two open-ended variables, and two continuous variables targeting socio-economics, bike trip characteristics, biking barriers, and preferred travel specifications. The results showed that the middle socio-economic group was more inclined, flexible, and willing to bike compared to the lower and higher socio-economic-groups. The lower socio-economic group used the bicycle more frequently than the middle socio-economic group. Around half of the middle socio-economic group commutes via bike compared to the lower socio-economic group. There was little to no representation of 55-64 and 65+ age groups in the data. The descriptive findings of this survey indicate some preliminary signs of differences of decisions and perceptions about biking compared to high-income and European countries. These differences need to be tested in future statistical analyses.